High pulse number thermal shock testing of tungsten alloys produced by powder injection molding - Th. Loewenhoff; S. Antusch; G. Pintsuk; M. Rieth; M. Wirtz (Nuclear Materials and Energy, 2019)
The investigation of plasma facing materials (PFM) subjected to a large number (≥10,000) of thermal shocks is of interest to determine long term morphological changes which might influence component lifetime in and plasma performance of a fusion reactor. The electron beam facility JUDITH 2 was used to simulate these conditions experimentally. In this study eight different tungsten grades produced by powder injection molding (PIM) were investigated: Two pure tungsten grades, one with 2 wt% Y2O3, three with 1, 2 and 3 wt% TiC, and two with 0.5 and 1 wt% TaC. Samples of 10 × 10 × 4 mm³ were brazed to a copper cooling structure and subjected to 105 thermal shocks of 0.5 ms duration and an intensity of Labs = 0.55 GW/m² (FHF = 12 MWs½/m2) at a base temperature of Tbase = 700 °C.The PIM grades showed damages in general comparable with a sintered and forged pure tungsten reference grade (>99.97 wt% W) that complies with the ITER specifications. One exception was the 2 wt% TiC doped material which failed early during the experiment by delamination of a large part of the surface. The Y2O3 doped material showed a comparatively good performance with respect to crack width (<15 μm) and roughening (Ra = 0.75 μm), but showed melt droplets of ∼3–4 μm diameter, while the 1 wt% TiC doped material showed wide cracks (up to 50 μm) and strong roughening (Ra = 2.5 μm). The paper discusses the post-mortem analysis of all grades, comparing them with respect to roughness (from laser profilometry), crack network characteristics and local melt droplet formation or other special morphological features (from SEM images) as well as crack depth (from metallographic cross sections). Keywords: Plasma facing material, Tungsten, Tungsten alloy, Powder injection molding (PIM), High heat flux